The Influence of Bank Specific Factors and Macro Economics on Non-Performing Financing in Islamic Rural Banks - Ramadhani, Rizkia; Mai, Muhammad Umar; Novianty, Ira (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
During 2017-2021, the BPRS NPF ratio has exceeded the threshold set by the Financial Services Authority, which is 7%. The average NPF ratio of BPRS for the 2017-2021 period is 8.25% (Otoritas Jasa Keuangan, 2022).. The population in this study are Islamic Rural Banks in Indonesia, namely 167 Islamic People's Financing Banka. The samples in this study were 157 Islamic Rural Banks. The sampling technique in this study used purposive sampling. Based on the discussion and results, ROA, CAR, FDR, Inflation, GDP, and unemployment on the dependent variable, namely NPF at Islamic Rural Banks during 2017-2021, the results show that ROA has a negative effect on NPF while FDR and inflation have a positive effect on NPF. Meanwhile CAR, GDP, and unemployment have no effect on NPF at Islamic Rural Banks in Indonesia.